Pharmacotherapy of obesity: state of the art and perspectives - Sićović, Katarina; Micov, Ana (Archives of Pharmacy, 2024)
Obesity is a chronic, progressive, and recurring disease. The prevalence of obesity has reached pandemic proportions, along with overweight-related conditions like diabetes, cardiovascular diseases, and certain cancers. Reducing residual morbidity is the main goal of obesity treatment. Pharmacotherapy is intended for patients who have not responded to lifestyle interventions. There are currently six anti-obesity medications (orlistat, phentermine/topiramate, naltrexone/bupropion, liraglutide, semaglutide, and tirzepatide) approved for long-term obesity management. Most of them, except orlistat, predominantly act centrally by increasing satiety, as well as reducing appetite and food reward. The most effective anti-obesity drugs are semaglutide and tirzepatide, which might provide weight loss of more than 10% of the initial weight. Although all anti-obesity medications have been demonstrated to improve cardiometabolic risk factors, only liraglutide and semaglutide lower the risk of major cardiovascular events in patients with or without established cardiovascular disease. A personalized approach, considering both drug (weight-reducing capacity and drug safety) and patient (comorbidities, age, and the patient’s preferences) features, guarantees the best results. In this article, we will critically appraise the efficacy and safety of currently approved anti-obesity medications and those in the pipeline.